The Cloister, Mystic Privations and the Conflictive Negotiation of Subjectivity in Lastenia Larriva de Llona's Un drama singular (1888). Issue 2 (February 2018) - Clark, Emily Joy
Abstract : During the nineteenth century an increase in the number of Hispanic women writers offered readers a diversity of opinions on the texts they published. Beginning in the 1870s in Peru, crucial authors such as Clorinda Matto de Turner and Mercedes Cabello de Carbonera provided readers with new perspectives on women's roles that have been popular with modern critics, but their views formed only part of the conversation. Peruvian Lastenia Larriva de Llona figures as one of the more conservative women of this generation, but her novel Un drama singular (1888), while problematic, still offers a subtle critique of society's poor treatment of women. By examining Larriva de Llona's writing through the lens of her Catholic faith, I show how religious practices such as cloistering and asceticism elucidate the novel's relationship to a tradition of religious women's writing and highlight society's mistreatment of marginalized women, unveiling a distinct perspective for readers.